Opportunities Abound: Stay Connected to Healthcare Initiatives- - Patricia O'Connor (Nursing Leadership, 2004)
In this issue of the journal, I'd like to give you an update on recent activities of the Academy of Canadian Executive Nurses, as well as other organizations supporting nursing leadership development. So often, nurses remain unaware of important national-level initiatives, for a variety of reasons. There are many websites to which you can subscribe without cost (or "bookmark as favourites") to stay in the loop and to ensure you don't miss important opportunities, such as access to national scholarships, bursaries, research grants and position papers or statements that could help support changes you would like to see in your practice or organization.